2021
DOI: 10.54203/scil.2021.wvj79
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Nutrient Digestibility, Biochemical Properties, Hematological Traits, and Intestinal Histopathology of Broiler Chicks Fed Mannan Oligosaccharides

Abstract: , , , , and Antibiotics as growth promoters in poultry diets are currently restricted, so other feed additives, such as prebiotics and probiotics, have been suggested as an antibiotics alternative to improve the performance and gut health of poultry. The current experiment was conducted to study the effects of adding Mannan oligosaccharides (MOS) as a potential replacement for an antibiotic on productive performance, nutrient digestibility, some blood parameters, and caecal microbiota of broiler chickens. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…The increased villi height and villus/crypt ratios indicated the increased turnover of intestinal epithelial cells and the stimulated blood circulation of the intestine [ 9 , 105 ]. On the contrary, our results disagreed with [ 106 ], who stated that lincomycin-supplemented broilers revealed necrosis of intestinal villi tips and massive inflammatory cell infiltration in intestinal propria and submucosa.…”
Section: Discussioncontrasting
confidence: 99%
“…The increased villi height and villus/crypt ratios indicated the increased turnover of intestinal epithelial cells and the stimulated blood circulation of the intestine [ 9 , 105 ]. On the contrary, our results disagreed with [ 106 ], who stated that lincomycin-supplemented broilers revealed necrosis of intestinal villi tips and massive inflammatory cell infiltration in intestinal propria and submucosa.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the ratio of neutrophils to lymphocytes as a biomarker of inflammation was increased by E. coli infection. Similarly, the previous study reported that supplementation of mannan-oligosaccharide (MOS) decreased the neutrophils in broilers (42).…”
Section: Discussionmentioning
confidence: 64%
“…Along with probiotics, it also has enough levels of vitamin B12, beta-carotene, and vitamin A [3]. The Azolla plant is a plant that co-occurs with the blue-green algae Anabaena azollae and is an excellent source of protein, is simple to produce, very productive, and has a high nutritional value [4]. [3] noticed that the broilers' productive performance greatly enhanced and their feed consumption decreased when 10% Azolla was used.…”
Section: Introductionmentioning
confidence: 99%